2012
DOI: 10.1111/j.1759-7714.2011.00083.x
|View full text |Cite
|
Sign up to set email alerts
|

Nimotuzumab combined with gemcitabine and cisplatin as second‐line chemotherapy for advanced non‐small‐cell lung cancer

Abstract: Objective: To evaluate the efficacy and safety of nimotuzumab combined with gemcitabine and cisplatin as second-line chemotherapy for advanced non-small-cell lung cancer (NSCLC) and to investigate the association of the status of KRAS gene mutation and epidermal growth factor receptor (EGFR) genotype with clinical outcome. Methods: Twenty-eight patients with advanced NSCLC were enrolled in this single center, uncontrolled pilot clinical study. All the patients developed drug resistance or disease progression a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 39 publications
2
10
0
Order By: Relevance
“…The docetaxel and carboplatin combination when administered to patients with stage IIIB/IV NSCLC resulted in an overall survival of 9.2 months27 and 9.4 months28 in two separate studies. Nimotuzumab in combination with gemcitabine and cisplatin as second-line therapy offered a median overall survival of 9.8 months 23. In our study, like overall survival, there were no significant between-group differences in progression-free survival ( P =0.31); the median progression-free survival of 4.9 months achieved in the nimotuzumab group was comparable with that of 4.44 months observed in another study using cetuximab in combination with a taxane 26…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…The docetaxel and carboplatin combination when administered to patients with stage IIIB/IV NSCLC resulted in an overall survival of 9.2 months27 and 9.4 months28 in two separate studies. Nimotuzumab in combination with gemcitabine and cisplatin as second-line therapy offered a median overall survival of 9.8 months 23. In our study, like overall survival, there were no significant between-group differences in progression-free survival ( P =0.31); the median progression-free survival of 4.9 months achieved in the nimotuzumab group was comparable with that of 4.44 months observed in another study using cetuximab in combination with a taxane 26…”
Section: Discussionsupporting
confidence: 79%
“…A study evaluating the efficacy of nimotuzumab plus gemcitabine and cisplatin as second-line therapy in patients with advanced NSCLC reported a response rate of 25% 23. In the Phase III FLEX (First-Line ErbituX in lung cancer) trial, treatment with cetuximab combined with cisplatin and vinorelbine resulted in a 36% overall response rate (measured by World Health Organization criteria) compared with 29% achieved with chemotherapy alone 25.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[11][12][13][14][15] When combined with RT, nimotuzumab (200 mg/week) showed few side effects 16 and improved the disease control rate in GBM patients, as compared with patients treated with RT alone. 17 A randomized, multicenter phase III trial in Europe showed that nimotuzumab (400 mg, weekly) on top of the current standard radiochemotherapy with TMZ followed by biweekly infusions of 400 mg nimotuzumab, was well tolerated in newly diagnosed GBM patients, substantially improving their quality of life and showing a clear trend toward efficacy in O6-methylguanine-DNA methyltransferase (MGMT) non-methylated GBM patients.…”
Section: Immunohistochemical Detection Of Egfrmentioning
confidence: 99%
“…The other one is a humanized monoclonal antibody that directly binds the extracellular domain of the EGFR (nimotuzumab) [42]. Interestingly, promising results in advanced NSCLC patients treated with CIMAVax-EGF [43,44] or nimotuzumab [45,46] has been obtained. In this way, the evaluation of mucin production in NSCLC patients after CIMAVax-EGF or nimotuzumab treatment seems to be of utmost importance.…”
Section: Discussionmentioning
confidence: 99%